Facial profile changes due to bone cement graft to manage the hyperactive muscles of the gingival smile - Érica Miranda de Torres; José Valladares-Neto; Karina de Oliveira Bernades; Luis Fernando Naldi; Hianne Miranda de Torres; Alexandre Leite Carvalho; Carlos Estrela
ABSTRACT Objective: To evaluate facial profile changes promoted by polymethyl methacrylate (PMMA) cement graft to reduce excessive gingival display due to hyperactivity of the elevator muscles of the upper lip during smiling. Methods: Eleven patients (all females, age range: 20 to 43 years) presenting gingival smile that were treated with PMMA cement grafts in a private clinic were selected for this retrospective study. Three angular and ten linear cephalometric facial profile measurements were performed preoperatively (baseline, T1) and at least 6 months postoperatively (T2). Differences between T1 and T2 were verified by Wilcoxon test, and the correlation between the thickness of the graft and facial profile changes was statistically evaluated by Spearman's Coefficient test. The significance level was set at p< 0.05. Results: The nasolabial angle (p= 0.03) and the labial component of the nasolabial angle showed statistically significant differences (p= 0.04), with higher values in T2. No correlations were found between the graft thickness and the statistically significant facial profile changes (p> 0.05). Conclusions: The PMMA bone cement graft projected the upper lip forward, thereby increasing the nasolabial angle without affecting the nasal component. No correlations between the graft thickness and the facial profile changes were detected.